INOVASI PERTANIAN BERKELANJUTAN: PELATIHAN PESTISIDA NABATI DAUN MIMBA UNTUK PETANI DI DESA LOWAYU, GRESIK - Zamzam, Alif Firdaus; Rodli, Rodli; Sabillah, Ifadatus; Sari, Virda Nawang; Zulhaq, Muhammad Hanif (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
The agricultural sector in Indonesia plays a crucial role in food security and the national economy. However, farmers face significant challenges related to pest and disease management. Excessive use of synthetic pesticides contributes to pest resistance, environmental pollution, and health risks. Amid global trends towards sustainable agriculture and organic products, Lowayu village, in East Java, faces issues such as limited water resources, resistant pest attacks, and high dependence on chemical inputs. The abundant potential of neem trees (Azadirachta indica) in the village offers an alternative solution as a botanical pesticide. This community service program aims to empower farmers in Lowayu by training them to produce botanical pesticides from neem leaves. The training, conducted by a team from Kuliah Kerja Nyata (KKN) program of Universitas Islam Darul 'Ulum Lamongan, involved problem screening, strategy formulation, experimentation, training, and evaluation. The results show high enthusiasm from participants, with 80% understanding the material well and 60% expressing interest in applying the method. Despite challenges such as variability in effectiveness and product consistency, this botanical pesticide's economic and environmental benefits are significant. This program successfully increased farmers' awareness of eco-friendly alternatives and provided a foundation for further development.